Escrita-corpo e as fabulações de gênero em ambientes digitais - Albuquerque, Patrícia Montenegro Matos (2020)
The research aims to reflect about on-line self writings produced by individuals which narrative projects has as central theme their gender dissident condition. The objective is to identify in which ways these narratives are constituted and how they operate as a potent technology to reconfigure or even to fray concepts and discursive practices apparently tight, tensing certain dichotomies. Our hypothesis is that these narratives are corpusmedia that build images and body singularities that reverberate activating other fabulations and perceptions of gender and sexuality. The self-writing, an aesthetics of existence, just like Foucault identified in Classic Antiquity will be an important key of lecture for the conduction of the work. The way Margareth Rago and Margaret McLaren and other authors updated this concept, to think about different empirical dimensions, will serve as theoretical and methodological forms of analysis. The feminist and gender studies, Queer and Corpusmedia Theory compose the epistemological object that will ground the research, in order to identify how such languages act, producing subjectivities that move between on-line and off-line life. Finally, we expect to apprehend the way these techno-interactive realities allow us to develop new possibilities for the analysis of culture through the relations of communicability and its political dimensions